Instagram and Traumatic Spine Injury: An Analysis of Social Media Altmetrics - Farooq, Minaam; Badary, Amr; Sadia, Haleema; Khan, Muhammad Huzaifa Ahmed; Tariq, Sunaina; Ahmed, Anas; Zahra, Shah Gul; Ranjha, Kaleem Ullah (Asian Journal of Neurosurgery, 2025)
With social media's increasing prevalence, platforms like Instagram have emerged as key sources of altmetrics. This study aimed to analyze the posts shared on Instagram referencing traumatic spine injury in terms of account type, languages, geographical distribution, content analysis, and audience engagement.Public Instagram posts were isolated and evaluated using the hashtags “#spinetrauma,” “#spinefracture,” “#spinetraumasurgeries,” “#spinalcordinjuryrecovery,” “#spinetraumasurvivor,” and “#spinalcordinjury.” The authors analyzed the top 1,000 posts for the variables: account type, languages, geographical distribution, content analysis, and audience engagement. In total, 345 posts were included for analysis using SPSS (version 26).Of the 345 Instagram posts and reels (Ps and Rs) that met our eligibility requirements, 183 (53%) were written in English. Surgeons' and physicians' accounts contributed 210 Ps/Rs (60.8%), while patients' accounts amounted to 63 Ps/Rs (18.3%). Out of 263 Ps/Rs with a known country of origin, the United States had the highest number with 56 Ps/Rs (16.2%). Content analysis revealed 114 Ps/Rs (33%) focused on pathology and 118 Ps/Rs (34.2%) posted radiological images. Regarding audience engagement, the survivor stories had the highest mean likes and comments per post, 126.5 (p = 0.107) and 8.7 (p = 0.018), respectively. It was followed by pathology-related content (mean likes/posts: 117.4 [p = 0.015], mean comments/post: 6.9 [p = 0.003]).Reported traumatic spine injury-related content has not been evaluated through social media avenues. This analysis demonstrates the leading role of surgeons in posting and educating the audience regarding traumatic spine injury, with the highest audience interest in survivor stories and pathologies. Our findings advance our knowledge of how social media portrays spine trauma, highlighting opportunities for future research and emphasizing the need for careful consideration of ethical and methodological challenges in social media studies related to medicine.
Keywords: Instagram; spine; traumatic spine injury; social media; spine fracture